2019
DOI: 10.1007/s13205-019-1880-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the rice J-protein family: identification, genomic organization, and expression profiles under multiple stresses

Abstract: J-proteins which function as molecular chaperone played critical roles in plant growth, development, and response to various environment stresses, but little was reported on this gene family in rice. Here, we identified 115 putative rice J-proteins and classified them into nine major clades (I-IX) according to their phylogenetic relationships. Gene-structure analysis revealed that each member of the same clade has same or similar exon-intron structure, and most rice J-protein genes of clade VII were intronless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…Only samples of healthy (mock-inoculated) tissues were analysed here. In the work of Luo et al [ 62 ], the heat stress treatment was applied for 1, 3, 6, 12, and 24 h after the 0 h control. To take full account of the time-of-day variations in gene expression due to photoperiod [ 95 ] and circadian control [ 96 ], only time points 0 h (control) and 24 h (heat stress) were analysed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only samples of healthy (mock-inoculated) tissues were analysed here. In the work of Luo et al [ 62 ], the heat stress treatment was applied for 1, 3, 6, 12, and 24 h after the 0 h control. To take full account of the time-of-day variations in gene expression due to photoperiod [ 95 ] and circadian control [ 96 ], only time points 0 h (control) and 24 h (heat stress) were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…The following are available online at https://www.mdpi.com/article/ 10.3390/plants10081647/s1, Figure S1: Distribution of the number of genes (y-axis) per number of transcripts per gene (x-axis) before (red) and after (blue) filtering low expressed transcripts and genes using the RNA-seq data extracted from Luo et al [62]; Figure S2…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, HSP70 in peanut was increased in abundance in response to drought [32]. DnaJ homolog proteins are essential components in the chaperone machine and could be induced by cold [33], heat [34], and drought stresses [35,36]. Other studies showed that several HSPs, co-chaperone DnaJ, and Grp chaperonin 60b were differentially altered under drought conditions [37,38].…”
Section: Stress and Defense Protein Abundance Under Drought Stressmentioning
confidence: 99%